Development of Teaching Module Plan Guidebook for Senior High School Teachers - Hasmawati, Hasmawati; Zakariah, M. Askari; Iqbal, Muh (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to develop a guidebook for designing teaching modules for Islamic Education (PAI) teachers at SMAIT Al Mawaddah Warrahmah Kolaka to enhance the quality of learning. The research utilized the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The validity of the product was tested through assessments by media and content experts, while practicality and effectiveness aspects were evaluated through field trials involving PAI teachers. The results indicate that the guidebook achieved a very high validity level, with an average score of 4.18 from media experts (83.7%) and 4.14 from content experts (82.8%). The practicality aspect was rated very good, with an average score of 4.12 (82.8%), highlighting that the guidebook is engaging and beneficial for teachers. Furthermore, the effectiveness test showed a significant improvement in teachers' understanding of module design, with the average score increasing from 3.6 (categorized as "Good") to 4.5 (categorized as "Very Good") after using the guidebook. These findings indicate that the developed guidebook is valid, practical, and effective for classroom implementation. The study's implications include strengthening teachers' capacity to design innovative learning and contributing to Islamic education literature in the context of module development. Further development is recommended to ensure the guidebook’s flexibility across various educational contexts and school levels.